Alveolar Rhabdomyosarcoma in a 69-Year-Old Woman Receiving Glucagon-Like Peptide-2 Therapy - Laura E. Zyczynski; Jonathan B. McHugh; Thomas E. Gribbin; Scott M. Schuetze (Case Reports in Oncological Medicine)
A 69-year-old woman was diagnosed with alveolar rhabdomyosarcoma (ARMS) of the nasopharynx. She has a history of catastrophic thromboembolic event in the abdomen that caused short-gut syndrome and dependence on total parenteral nutrition (TPN) twelve hours per day. She was treated for short-gut syndrome with teduglutide, a glucagon-like peptide-2 (GLP-2) analog, which led to reduction of TPN requirements. However, a few months later, she developed metastatic alveolar rhabdomyosarcoma. Though a causative relationship is unlikely between the peptide and ARMS due to the brief time course between teduglutide therapy and sarcoma diagnosis, neoplastic growth may have been accelerated by the GLP-2 analog, causing release of IGF-1. The transmembrane receptor for IGF-1 is frequently overexpressed in ARMS and is implicated in cell proliferation and metastatic behavior. This case describes a rare incidence of metastatic alveolar rhabdomyosarcoma in a sexagenarian and possibly the first case reported associated with the use of teduglutide. Teduglutide was discontinued due to a potential theoretical risk of acceleration of sarcoma growth, and the patient’s rhabdomyosarcoma is in remission following sarcoma chemotherapy.